Health conditions oral disease in indigenous and non-indigenous pregnant adolescents from Maracaibo- Venezuela. - Quintero De La Hoz, Tomás Enrique (2022)
Objective: Compare the oral disease health conditions in indigenous and non-indigenous pregnant adolescents from Maracaibo-Venezuela. Material and Methods: It was an epidemiological, cross-sectional study with a field design, not experimental. The sample was 121 pregnant adolescents from the prenatal consultation of the Maternal and Child Hospital “Eduardo Soto Peña” and the Maternity “Dr. Armando Castillo Plaza” in Maracaibo. Clinical examination was performed according to the criteria of the World Health Organization, DMFT, SCI, SOH-I and PCI indexes were measured. SPSS® version 25 software was used to process the data and both the t-test for independent samples and Chi square were applied. Results: the caries experience was 91.7%, the DMFT index was 6.84 ± 4.173 and the SCI was 11.42 ± 2.374. For the periodontal condition, 41.3% had a healthy condition, 53.7% had gingivitis and 5% had periodontitis. The group of non-indigenous pregnant women had a higher DMFT index of 7.19 ± 4.066 ccompared to 5.52 ± 4.398 for indigenous women. Regarding the consolidated periodontal condition, 52% of the indigenous group presented gingivitis and the rest were healthy and among the non-indigenous 54% presented gingivitis, 6% had periodontitis and 40% was healthy. Conclusion: In this study, no differences were observed between the oral disease health conditions of indigenous and non-indigenous pregnant adolescents. However, it is necessary to give priority to the attention of the oral component of adolescent girls during pregnancy.